Comparative Study of Pure Mg and AZ91D as Sacrificial Anodes for Reinforced Cement Concrete Structures in Chloride Atmosphere - Yogesh Iyer Murthy; Sumit Gandhi; Abhishek Kumar (Salehan Institute of Higher Education, 2018)
Comparative study of the corrosion behavior of pure Magnesium and AZ91D anodes in reinforced cement concrete was undertaken in the present work. The steel reinforcements were kept in contact with these anodes electrochemically in chloride atmosphere and the half-cell potential drop was observed. Bare steel reinforcements were tied to the anodes and were also kept in high chloride atmosphere to test the mechanical properties. The yield stress and ultimate tensile stress were found to decrease by approximately 50MPa while the reduction in percentage elongation is approximately 25% for reinforcements tied to AZ91D and pure Mg at the end of 80 days compared to fresh steel reinforcement. The rate of corrosion of pure Mg was reportedly slightly higher compared to AZ91D due to the presence of inter-metallics as inferred through micro-graphs.